Experimental Study on Seismic Response of Buried Oil and Gas Pipeline Soil Layers under Lateral Multipoint Excitation - Jianbo Dai; Li Wang; Chengtao Hu; Guidi Zhang (Shock and Vibration)
The seismic response of buried oil and gas pipelines is mainly influenced by the site soil. In this paper, a bidirectional laminar shear continuum model box is developed for the site response of buried oil and gas pipelines under transverse multipoint seismic excitation. By comparing the acceleration response of the soil and pipeline, monitoring the soil displacement, and analyzing the acceleration coefficient and Fourier spectrum, the seismic response characteristics of the soil at different excitation modes and peak seismic acceleration and its laws were investigated. The test results show that the soil under transverse excitation undergoes the process of soil compaction to nonlinear characteristics and finally soil damage, and the course of multipoint excitation develops faster and causes more serious soil damage. The peak Fourier spectrum of both the pipe and the soil appears at the frequency of 4–6 Hz, and in general, the acceleration of the pipe is greater than that of the soil; the difference between the two gradually decreases with the increase of loading level. Compared with the uniform excitation, the increase in the loading level during the lateral multipoint excitation will result in a decrease of the consistency of the acceleration time history curve at each measurement point and a decrease of the peak of the spectrum. The effect of laminar shear between soil bodies becomes more obvious with the increase of acceleration peaks on the shaking table. It is also found out that the excitation method has little effect on the displacement time history curve, but the multipoint excitation may cause fluctuations in the displacement time history curve.